Kebijakan Pemerintah Australia dalam Menangani Isu Food Waste dan Food Loss di Australia pada Tahun 2017-2019 - Rozzana, Beatrix Engueline; Wiranata, I Made Anom; Widya Nugraha, A.A. Bagus Surya (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL); Vol 4 No 1 (2024): JURNAL DIKSHI, 2024)
Food waste is the most recent phenomenon that bring attentions from every environmentalist, especially international food and agricultural organization, FAO. The numbers of food waste, generate methane to the atmosphere. The methane that produced by those waste was as equal as fossil fuels produced. Therefore, FAO urge every food chain actors from farm to fork to be involved and manage their food for the better. This research describe the steps and policy that was created by Australia’s government to reducing the food waste and food loss issues in Australia, who also aiming to gives the educations and increasing the awareness of every Australian towards this issue with applicable methods to every involved actors in food chain. The purpose of reducing the food waste and food loss activity was as form of complicity of Australia on Paris Agreement to reducing the emission by the 2030. Keywords : Food Waste, Food Loss, Policy, Waste Management